The Right Time to Forget The Time: Waktu yang tepat untuk Melupakan Waktu - Zahwa Maylafaizzah Al Fatihah; Moses Glorino Rumambo Pandin (ARISTO, 2022)
What's fun about reading poetry? Everyone has their own way of enjoying poetry. Everyone can interpret a poem in their own way. Reading poetry can also be a way to relieve fatigue. Reading poetry can take us to spaces of feelings that we may never really understand before. Name of M Aan Mansyur in the Indonesian literature sector is certainly familiar. The poet from Bone, South Sulawesi, became increasingly popular when his poems were used in the What's with Love 2 (AADC 2) movie, which was released in 2016. Now, he is back to showing his latest work. A collection of poems entitled 'The Right Time to Forget the Time.' which released in last October 2021 by Shira Media Publishers.